Teritorialni del reforme lokalne samouprave v Sloveniji - Čokert, Andrej (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2005)
The reform of Slovene local self-government contains five components: functional, territorial, organisational,financial-material and legal. The article is analysing territorial component. The territorial component involves the establishment of new municipalities, which replaced the former communes. In 1994, 147 new municipalities were formed out of 62 communes, in 1998 another 45 municipalities were added and in 2002 one more. There are currently 193 municipalities in Slovenia which are not all formed according to the legislative criteria (5000 inhabitants).
Keywords: Slovenia; Slovenija; regije; regionalna politika; local government; lokalna samouprava